2021
DOI: 10.1590/0034-7167-2020-0200
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and non-pharmacological treatment of delirium in an oncological hospital service: an integrative review

Abstract: Objectives: to analyze the production of scientific articles about the pharmacological and non-pharmacological management of delirium in adult hospitalized cancer patients. Methods: integrative review whose sample was obtained from the databases Scopus, Cumulative Index to Nursing and Allied Health Literature, EMBASE, Web of Science, and from the portals Biblioteca Virtual em Saúde, and PubMed. Results: among the ten studies analyzed, 80% described exclusively the pharmacological management, especially with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…38 The goal in delirium management is; It includes presenting preventive approaches, identifying delirium risk factors and eliminating them if possible, and in the final stage, pharmacological and non-pharmacological management of delirium. 39 The use of non-pharmacological approaches is recommended as the first line of treatment in the management of delirium. 6,18 In the study, it was detected that only 17.5% of the nurses first used a non-pharmacological approach to delirium treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The goal in delirium management is; It includes presenting preventive approaches, identifying delirium risk factors and eliminating them if possible, and in the final stage, pharmacological and non-pharmacological management of delirium. 39 The use of non-pharmacological approaches is recommended as the first line of treatment in the management of delirium. 6,18 In the study, it was detected that only 17.5% of the nurses first used a non-pharmacological approach to delirium treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a review study evaluating the pharmacological and non-pharmacological management of delirium in oncology hospitals; It was found that in 80% of the ten studies analysed, delirium was managed with a pharmacological agent and haloperidol was used especially frequently in advanced stage cancer patients. 39 In a study evaluating the attitudes, beliefs and opinions of certified palliative care specialists and liaison psychiatrists towards hypoactive delirium in the last days of life; 62% of physicians stated that pharmacological drugs should be used in the management of hypoactive delirium. 40 In a study evaluating the practices of clinicians regarding delirium treatment in Australia; It has been interpreted that 79% of palliative care providers use antipsychotics in delirium management, and this is mainly due to distress and safety concerns for the patient and others nearby.…”
Section: Discussionmentioning
confidence: 99%
“…It also interferes with the patient's decision-making capacity, making shared decision-making significantly more complex [57]. The main treatment consists of non-pharmacological interventions focused on prevention [58,59]. However, when non-pharmacological interventions are insufficient, treatment with psychotropic drugs such as antipsychotics medications may be necessary [56].…”
Section: Deliriummentioning
confidence: 99%